Implementation Of The Al-Qur’an Literacy Education Program At The Darussalam Foundation, Cibubur Tourism City - Sugiarto Sugiarto; Hanifudin Aminullah ; Siti Rochanah (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Al-Quran Literacy Education is part of the development of a mosque, where the mosque becomes the center of education and worship for Muslims. The Qur’an is primary literature among Muslims, both used as guidance and worship. Moreover, Minister of Education and Culture Regulation No. 21 of 2016 concerning Educational Content Standards states that reading and understanding the Al-Qur'an is an important component in Islamic Religious Education. The reality is that the Al-Quran literacy index in Indonesia is not high, in fact tends to be low, there are around 60-70% of Indonesian Muslims who cannot read the Al-Qur'an. Therefore, the Darussalam Mosque in the tourist city is implementing a Qur'an literacy education program which is religious education to overcome Al-Qur'an illiteracy/Qur'an illiteracy for the community. The targets in this research is the Management of the Darussalam Mosque. The research method uses a qualitative descriptive approach. The results show that the educational service program is the Qur'an Workshop. The Qur'an Workshop program is a Qur’an learning education for elderly people ranging from 50-60 years and over as an effort to enlighten the Muslim community so that they can read and understand the holy book of the Koran as a guide to life based on activities taught by teachers at the mosque (ustadz and ustadzah) who really have the ability to teach Qur’anic literacy to the elderly community. The presence of the Qur'an workshop program is expected to be able to overcome the very high number of Qur'an illiteracy in the community.